ASPEK HUKUM PELAKSANAAN PERJANJIAN PINJAMAN DENGAN JAMINAN KENDARAAN BERMOTOR DI KOPERASI SIMPAN PINJAM (KSP) - Hermes, Christian Daniel; Nainggolan, Rosita; Sitinjak, Humala (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to determine what problems arise in the implementation of a loan agreement with motorized vehicle collateral in a Savings and Loan Cooperative, and how the settlement process is if the debtor defaults in the Savings and Loan Cooperative. This study analyzes data qualitatively. The approach method to this study is normative, which will examine the object systematically based on legislation to provide an opinion or legal argument in the form of legal rules that apply to certain legal events. The data source used is secondary data. The data collection tool used is a documentation study.  The problem that arises in the implementation of a motor vehicle collateral loan agreement in a cooperative is if the cooperative accepts a motor vehicle collateral that has a fiduciary obligation, while the cooperative does not re-register the vehicle collateral when making a savings and loan agreement with the debtor. So, if the customer or debtor is in default, as stated in the standard agreement of the cooperative, then the cooperative does not have the right of execution to resolve the problem. The settlement process if the debtor is in default, the cooperative will make efforts to resolve problematic credit through two methods, namely negotiation and litigation